Reasons and Benefits of Seasonal Migrations in the Villages of Rugova - KRASNIQI, Addhe; DANA, Hazer; ÇELA, Tomor (Journal of Environmental Management and Tourism; Vol 11 No 7 (2020): JEMT Volume XI Issue 7(47) Winter 2020, 2020)
This study deals with seasonal migration as a special frame of migration. These migrations date back to the early days and consist of the movement of the population for a certain period of time, which are mainly related to the grazing of animals in the hilly-mountainous areas for higher productivity. In the territory of Kosova, as well, this sort of migration is quite emphatic, specifically in Rugova Mountain (Albanian Alps). The basic purpose of this research is the evidence of the main reasons of seasonal migration and the benefits of it. It is quite apparent that the main reasons are economic in nature, therefore through this research the key factor why the migrations reside those high mountain areas during warm seasons have been analyzed. Moreover, beside those migration reasons, a special emphasis in this study is given to the benefits those migrations have been bringing to the immigrant country, as well as to the migrant one.